Time for Bed, Little Owls! - Alves, Katja; Stegmaier, Andrea; Lawson, Polly (Edinburgh, UK : Floris Books, 2024)
This interactive bedtime picture book asks young readers to clap, call and count as they help Mama Owl put her ten little owls to bed. A clever and cosy addition to any bedtime routine that is bound to leave little readers yawning and ready to sleep too.
Translated from the German
Keywords: Children's stories, German -- Translations into English; Owls -- Pictorial works -- Juvenile fiction; Bedtime -- Pictorial works -- Juvenile fiction; Picture books for children; Picture books